Cztery kolędy Ewy Lipskiej - Marciniak, Paweł (Poznańskie Studia Polonistyczne. Seria Literacka, 2018)
The article contains the reflection on four texts of Ewa Lipska, written in association with Zbigniew Preisner. The discussed works belong to a genre of a literary carol and as a result they have been included in the republication of the album W poszukiwaniu dróg [Searching for the paths ] Therefore, a new area of poetics activity of Lipska appears. The authoress of Sefer makes use of stylization, deforming a specified pattern and thereby revaluating the tradition of a carol. The scrutinised texts were designed as being ready for the musical performance, emphasising Lipska’s interest in the song genre. The creation of a Cracovian poetess has been tilting towards popular culture since some longer time now.